Landscape, surface runoff, and groundwater quality in the district of Puán, province of Buenos Aires, Argentina - Gonzalez Uriarte, Magdalena Juana (2002)
The Puán district in the southwest of the province of Buenos Aires covers an area of 6,385 km2 (2,465 mi2) and has a population of about 18,000 residing in small urban centers and rural areas where farming is the main economic activity. Owing to the absence of freshwater streams and the low level of rainfall, groundwater provides the principal source of water and is used for human and animal consumption, as well as for the growing network of supplementary irrigation. This paper gives an overview of the district's water resources by reporting on the landscape, surface runoff, and groundwater quality within the framework of six geomorphological environments. Groundwater depth, anion-cation content and principal pollutants are measured in representative samples from each geomorphological unit. Pollutants are divided into those of natural origin (arsenic-boron-fluoride) and those induced by anthrop activity. The results obtained provide a basis for the adequate planning of water management, taking into account the consequences of groundwater exploitation and the implementation of preventive measures where necessary.